Socio-emotional competence as a psychological component of an individual's social intelligence - Bedan , Viktoriia (Journal of Education, Health and Sport, 2025)
This article presents a theoretical and empirical analysis of the relationship between social intelligence and an individual's socio-emotional competence. Based on an analysis of contemporary scientific approaches, the relationship between these psychological phenomena is clarified, and the appropriateness of considering socio-emotional competence as an important psychological component of social intelligence is substantiated. It is shown that social intelligence provides a cognitive understanding of social situations and of other people's motives and behavior, whereas socio-emotional competence reflects an individual's ability to put this understanding into practice through emotional self-regulation, empathy, social management, and effective interpersonal interaction. The empirical study involved 76 respondents aged 18 to 23 and used J. Guilford's Social Intelligence Test and A. Shashenkova's Socio-Emotional Competence Questionnaire. Correlation analysis and the method of contrasting groups were used to analyze the results. Statistically significant relationships were identified between individual components of socio-emotional competence and indicators of social intelligence. The strongest relationships were found for the scales of socio-emotional awareness, social management, and self-efficacy. Individuals with high levels of social intelligence were shown to have higher scores on every component of socio-emotional competence than individuals with low levels of social intelligence. The findings confirm that socio-emotional competence is an important psychological component of social intelligence that contributes to the effectiveness of social cognition, interpersonal interaction, and social adaptation.